Quantifying the performance of dual-use rainwater harvesting systems. (1st January 2021) - Quinn, Ruth; Rougé, Charles; Stovin, Virginia
Abstract: Rainwater harvesting systems in urban settings are increasingly relied upon to mitigate pluvial flooding on top of providing an additional water supply. Alternative designs have been proposed to support their dual use. Stormwater management performance is typically evaluated through long-term averages. However, long-term assessment is not aligned with the goal of attenuating the impacts of short duration high-intensity rainfall events. This paper contributes a framework for evaluating the dual-use performance of design alternatives. The framework incorporates a set of stormwater management metrics that provides a robust characterisation of performance during significant rainfall events. To the usual long-term volumetric retention metric, we add: 1) metrics that represent the total volume and duration above predevelopment (greenfield) runoff rates; and 2) robust peak outflow rate and retention efficiencies based on the long-term median of a representative sample of significant rainfall events. Our multi-criteria performance visualisations of alternative dual-use designs highlight the importance of carefully designing the forecast-based controlled release mechanisms built into active systems. This work has direct implications for design guidance standards, which we discuss. Graphical abstract: Image 1 Highlights: Existing RWH performance metrics ignore storm event-based runoff quantities. We propose a framework comprising seven performance metrics. Stormwater control metrics address routine and significant event performance. The sensitivity of performance metrics to demand is configuration specific. A flow duration curve may provide a suitable basis for regulatory standards.